PERANCANGAN SISTEM PELAPORAN MANAJEMEN PERUSAHAAN DAERAH BANK PERKREDITAN RAKYAT BANK PASAR KABUPATEN BANTUL (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
This research entitled Design System of Management Reporting in Perusahaan Daerah Bank Perkreditan Rakyat Bank Pasar Kabupaten Bantul. This system is designed using Microsoft Access with identify system documentation to 3 level management with modeling data. Afterwards modelling process using clasify database each division in fiield by observe and interview. Furthermore modeling object by connecting with table realtion of database to syncronization all data to present on reporting of management. The result of this design is the interface are easy to use, fully access data information for top level management & and reducing time to decision making in middle level management. By presenting accuracy and reliable information of the management report will achieved the target.